Reverse Total Shoulder Arthroplasty for Proximal Humerus Fracture. Issue 3 (September 2016) - Chuinard, Christopher
Abstract : Reverse shoulder arthroplasty (RSA) has gained wide acceptance for its primary indication, cuff tear arthropathy. The last 5 years, however, has seen the utilization of RSA increase, dramatically, as one of the preferred methods for treating proximal humeral fractures in the elderly. By utilizing surgical techniques that focus on tuberosity reconstruction, excellent results can be see with reverse shoulder replacement for fracture; in fact, RSA for fracture has demonstrated more reliable outcomes than hemiarthroplasty for fracture and is favored in the elderly population.